The self-assessment of critical thinking disposition and the needs for training: a cross-sectional survey of clinical nurses - Gao, Kailun; Zhong, Xiaotong; Zhang, Yingying; Wang, Min; Chen, Ling; Cai, Wenzhi; Ren, Wei (Frontiers in Medicine, 2025)
BackgroundCritical thinking is essential for nurses’ clinical decision-making and the delivery of safe, high-quality care, and is shaped by their critical thinking disposition. However, nurses demonstrate negative critical thinking dispositions, with limited evidence available on influencing factors and training needs.ObjectiveThis study aims to investigate nurses’ critical thinking dispositions, identify influencing factors, and explore their relationship with training needs.MethodsA cross-sectional study was conducted in three tertiary Grade A hospitals from January to February 2025. Nurses were asked to complete the Chinese version of the critical thinking disposition inventory and a self-designed training needs questionnaire. Descriptive statistics, correlation analysis, and multiple regression analysis were performed.ResultsA total of 370 clinical nurses participated in this study. The average critical thinking disposition score was 281.58 ± 36.68 and training needs score was 90.94 ± 12.01. Age, working experience, professional level, specialist nurse, position, department, and health status significantly influenced critical thinking disposition (all p < 0.05). Multiple linear regression analysis showed health status and position being the most significant contributors (R2 = 0.128, p < 0.001). Notably, a significant positive correlation was observed between nurses’ critical thinking disposition and their training needs (r = 0.358, p < 0.01).ConclusionThese findings highlight the necessity of aligning education with individual needs. By implementing tailored training programs, nurses can be better supported the development of critical thinking, thereby fostering safer and higher-quality clinical practice.